Prescription characteristics associated with fall-related injury risk among older adults prescribed benzodiazepines: a cohort study - Donovan T. Maust; Amy S. B. Bohnert; Julie Strominger; Neil Alexander; Lillian Min; Geoffrey J. Hoffman; Jason E. Goldstick (BMC Geriatrics, 2022)
Abstract Background Benzodiazepines (BZD) are widely prescribed to older adults despite their association with increased fall injury. Our aim is to better characterize risk-elevating factors among those prescribed BZD. Methods A retrospective cohort study using a 20% sample of﻿ Medicare beneficiaries with Part D prescription drug coverage. Patients with a BZD prescription (“index”) between 1 April 2016 and 31 December 2017 contributed to incident (n=379,273) and continuing (n=509,634) cohorts based on prescriptions during a 6-month pre-index baseline. Exposures were index BZD average daily dose and days prescribed; baseline BZD medication possession ratio (MPR) (for the continuing cohort); and co-prescribed central nervous system-active medications. Outcome was a treated fall-related injury within 30 days post-index BZD, examined using Cox proportional hazards adjusting for demographic and clinical covariates and the dose prescribed. Results Among incident and continuing cohorts, 0.9% and 0.7% experienced fall injury within 30 days of index. In both cohorts, injury risk was elevated immediately post-index among those prescribed the lowest quantity: e.g., for <14-day fill (ref: 14-30 days) in the incident cohort, risk was 37% higher the 10 days post-fill (adjusted hazard ratio [HR] 1.37 [95% confidence interval [CI] 1.19-1.59]). Risk was elevated immediately post-index for continuing users with low baseline BZD exposure (e.g., for MPR <0.5 [ref: MPR 0.5-1], HR during days 1-10 was 1.23 [CI 1.08-1.39]). Concurrent antipsychotics and opioids were associated with elevated injury risk in both cohorts (e.g., incident HRs 1.21 [CI 1.03-1.40] and 1.22 [CI 1.07-1.40], respectively; continuing HRs 1.23 [1.10-1.37] and 1.21 [1.11-1.33]). Conclusions Low baseline BZD exposure and a small index prescription were associated with higher fall injury risk immediately after a BZD fill. Concurrent exposure to antipsychotics and opioids were associated with elevated short-term risk for both incident and continuing cohorts.